Sarcopenia as a prognostic marker in patients undergoing pancreaticoduodenectomy: an updated meta-analysis - He, Jie; Li, Jia; Liu, Jia; Liu, Meng (Frontiers in Oncology, 2025)
BackgroundSarcopenia is prevalent among patients undergoing pancreaticoduodenectomy (PD). However, the effect of sarcopenia on postoperative complications and the prognosis of patients undergoing PD remain controversial. This meta-analysis aimed to evaluate the potential use of sarcopenia as a prognostic indicator in patients undergoing PD.MethodsA systematic search was conducted using the databases of Web of Science, EMBASE, China National Knowledge Infrastructure, Cochrane Library, and PubMed from inception to March 14, 2025, to identify studies on sarcopenia in patients undergoing PD. The pooled prevalence of sarcopenia and its 95% confidence interval (CI) were calculated, and heterogeneity was assessed using the I² test. Associations between sarcopenia and major postoperative complications, postoperative pancreatic fistula (POPF), postoperative biliary fistula (POBF), mortality, disease-free survival (DFS), and overall survival (OS) were expressed as odds ratios (ORs) or hazard ratios (HRs) with 95% CIs. Statistical analyses were performed using Stata version 11.0.ResultsThis meta-analysis included 30 articles involving 5,323 participants. The prevalence of sarcopenia before PD was 35%. Patients with sarcopenia exhibited a significantly higher risk of major complications (Clavien–Dindo [CD] grade ≥ III) (OR = 1.84, 95% CI = 1.26–2.69, P = 0.002), POPF (OR = 1.47, 95% CI = 1.13–1.93, P = 0.004), and POBF (OR = 1.53, 95% CI = 1.05–2.25, P = 0.028) than those without sarcopenia. In addition, postoperative mortality was higher in patients with sarcopenia (OR = 3.52, 95% CI = 2.01–6.19, P = 0.002). Patients without sarcopenia exhibited better DFS and OS after PD than those with sarcopenia (DFS: HR = 2.28, 95% CI = 1.18–2.88, P < 0.001; OS: HR = 3.15, 95% CI = 2.49–3.98, P < 0.001).ConclusionA high proportion of patients presented with sarcopenia before undergoing PD. Patients undergoing PD with sarcopenia face a higher risk of overall incidence of major complications (CD grade ≥ III), POPF, POBF, and mortality, and they exhibit worse DFS and OS than those without sarcopenia. Future studies should adopt stricter definitions of sarcopenia to further validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025635939, identifier CRD42025635939.